2016
DOI: 10.3390/metabo6030026
|View full text |Cite
|
Sign up to set email alerts
|

Specific Metabolome Profile of Exhaled Breath Condensate in Patients with Shock and Respiratory Failure: A Pilot Study

Abstract: Background: Shock includes different pathophysiological mechanisms not fully understood and remains a challenge to manage. Exhaled breath condensate (EBC) may contain relevant biomarkers that could help us make an early diagnosis or better understand the metabolic perturbations resulting from this pathological situation. Objective: we aimed to establish the metabolomics signature of EBC from patients in shock with acute respiratory failure in a pilot study. Material and methods: We explored the metabolic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Although the use of biological fluid metabolites for diagnosis of medical conditions has been in existence since ancient times, modern metabolomics analysis began in the mid-1980s with the development of higher-sensitivity nuclear magnetic resonance spectroscopes (47). Metabolites are small molecules up to~1,000 Da and include a spectrum of compounds such as organic acids, amino acids, carbohydrates, peptides, vitamins, steroids, and xenobiotics, among others (24). The fundamental premise in metabolomics analyses is that changes, whether physiological or pathological, cause alterations in the metabolome that are detected as variations in metabolite concentrations.…”
Section: What Is Metabolomics?mentioning
confidence: 99%
“…Although the use of biological fluid metabolites for diagnosis of medical conditions has been in existence since ancient times, modern metabolomics analysis began in the mid-1980s with the development of higher-sensitivity nuclear magnetic resonance spectroscopes (47). Metabolites are small molecules up to~1,000 Da and include a spectrum of compounds such as organic acids, amino acids, carbohydrates, peptides, vitamins, steroids, and xenobiotics, among others (24). The fundamental premise in metabolomics analyses is that changes, whether physiological or pathological, cause alterations in the metabolome that are detected as variations in metabolite concentrations.…”
Section: What Is Metabolomics?mentioning
confidence: 99%
“…In this regard, F ermier et al . [ 21 ] performed an EBC metabolomics study in which they accurately discriminated critically ill MV patients and MV surgical patients. The investigators, however, reported conflicting values of EBC yield (1 mL versus 2–3 mL per 20 min in their Methods and Results section, respectively, with no assignment to patient groups) and did not report the conditions of air humidification in their patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of humidification guidelines has resulted in inconsistent methodologies in studies of EBC from MV patients. While some investigators have collected EBC with ongoing air humidification [ 8 – 12 ], others have removed the humidifier from the ventilatory circuit prior to sample collection [ 13 20 ], and yet others have not reported their humidification conditions [ 21 29 ]. Importantly, M üller et al .…”
Section: Introductionmentioning
confidence: 99%
“…Towards the discovery of biomarkers and in the pursuit of improved disease characterization, metabolomics has been employed in lung diseases to study a large number of sample types including urine, plasma and serum, cerebrospinal fluid, exhaled breath condensate (EBC), bronchoalveolar lavage fluid (BALF), saliva, intact tissue as well as cells and their extracts. Urine and blood are the most commonly used biofluids for metabolomic studies as both samples contain thousands of detectable metabolic features and can be collected using minimally invasive methods.…”
Section: Metabolomic‐driven Discovery Of Biomarkersmentioning
confidence: 99%